2020
DOI: 10.1177/0003319720905751
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Mortality of Venous Leg Diseases of the Deep Veins: An Observational Cohort Study Based on German Health Claims Data

Abstract: This study estimates the prevalence and mortality of diseases of the deep veins of the legs such as deep vein thrombosis (DVT), postthrombotic syndrome (PTS), and venous leg ulceration (VLU). We used a random sample of 250 000 patients at age 50+ years of the register of the Allgemeine Ortskrankenkasse from 2004 to 2015. Selected manifestations of venous diseases assumed as risk factors for mortality were analyzed using Cox models while adjusting for various basic demographic and health characteristics. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 35 publications
2
18
1
1
Order By: Relevance
“…Also, Žulec et al [32] and Kirsner et al [33] found that VLU occurred among the elderly and verified that the majority of their cases were men. This was in contrast to previous findings by Kreft et al [34] and Jeanmonod et al [35] who reported that the majority of their sample was composed of elderly females. The comparison of the study and control groups' sociodemographic characteristics indicated no significant differences at baseline that might have influenced the findings; this implies that the two study groups were homogeneous.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, Žulec et al [32] and Kirsner et al [33] found that VLU occurred among the elderly and verified that the majority of their cases were men. This was in contrast to previous findings by Kreft et al [34] and Jeanmonod et al [35] who reported that the majority of their sample was composed of elderly females. The comparison of the study and control groups' sociodemographic characteristics indicated no significant differences at baseline that might have influenced the findings; this implies that the two study groups were homogeneous.…”
Section: Discussioncontrasting
confidence: 99%
“…According to Kreft et al (2020), in 2004 to 2015 the mortality rate in Germany for individuals with a VLU (C6) was 7.02 deaths/100 person-years. The same researchers found that individuals with VLU (C5-C6) had a 23% higher mortality risk than the general population.…”
Section: Differences In the Prevalence Study Methodsmentioning
confidence: 99%
“…The last stage of CVD (VLU C6) logically has the biggest impact on quality of life, health costs, and mortality risk. The estimated prevalence of C6 ranges from 0.1% to 3% of the population (Álvarez-Fernández et al, 2008;Berenguer Pérez, López-Casanova, Sarabia Lavín, González de la Torre, & Verdú-Soriano, 2019;Escudero Rodríguez et al, 2014;Kreft et al, 2020;Marinel•lo Roura & Verdú Soriano, 2018;Vuylsteke et al, 2015Vuylsteke et al, , 2018. Including all individuals who have an active or healed VLU (C5-C6), the prevalence has been estimated to be as high as 9.1% (Vuylsteke et al, 2018).…”
Section: Differences In the Prevalence Study Methodsmentioning
confidence: 99%
“…Here, the individual and social benefit, the gain in quality of life, and the related costs are being quantified. Demographic research, based on patient-related data, is used as a starting point for the differential assessment of alternative therapeutic concepts [7]. Influencing factors of the relevant German and international health markets, with their respective regulatory and reimbursement mechanisms, are being studied together with industry.…”
Section: Innovationsmentioning
confidence: 99%